Peripheral Arterial Thrombosis as an Atypical Initial Presentation of Systemic Lupus Erythematosus in a Young Male: A Case Report - Khan, Rohit; Nobi, Md Ayakub; Faruque, Abdullah Al; Ahsan, HM Nazmul (Bangladesh Journal of Medicine, 2025)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with heterogeneous clinical manifestations and a predilection for affecting women of childbearing age. Thrombotic events, particularly venous thrombosis, are well-documented complications of SLE, often associated with antiphospholipid syndrome (APS). However, arterial thrombosis, especially involving large peripheral vessels, is a relatively rare initial manifestation, and even more unusual in young males without traditional cardiovascular risk factors. We report the case of an 18-year-old previously healthy male who presented with acute peripheral arterial thrombosis of the superficial femoral artery. Given the patient's age and clinical presentation, a comprehensive evaluation for underlying prothrombotic and autoimmune etiologies was pursued. Comprehensive laboratory evaluation showed positive antinuclear antibody (ANA) and anti-double stranded DNA (anti-dsDNA) antibodies, with negative antiphospholipid antibodies and a normal thrombophilia panel. CT angiogram confirmed a long-segment thrombotic occlusion of the right superficial femoral artery. The diagnosis of SLE with vascular involvement was established in the absence of APS. The patient was successfully managed with immunosuppressive therapy and antiplatelet agents. This case highlights the diagnostic complexity of SLE in atypical presentations and emphasizes the importance of considering SLE in young patients with thrombotic events, even in the absence of classic risk factors. Bangladesh J Medicine 2025; 36(3): 160-163